Synchronization control of complex spatio-temporal networks based on fractional-order hyperbolic PDEs with delayed coupling and space-varying coefficients - Yang, Chengyan; Wang, Jin; Jian, Muwei; Dai, Jiashu (Multidisciplinary Digital Publishing Institute, 2024)
This paper studies synchronization behaviors of two sorts of non-linear fractional-order complex spatio-temporal networks modeled by hyperbolic space-varying PDEs (FCSNHSPDEs), respectively, with time-invariant delays and time-varying delays, including one delayed coupling. One distributed controller with space-varying control gains is firstly designed. For time-invariant delayed cases, sufficient conditions for synchronization of FCSNHSPDEs are presented via LMIs, which have no relation to time delays. For time-varying delayed cases, synchronization conditions of FCSNHSPDEs are presented via spatial algebraic LMIs (SALMIs), which are related to time delay varying speeds. Finally, two examples show the validity of the control approaches.